Methods and Tools for the Formation of Knowledge, Skills and Abilities of Weak Hearing Students (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the article, the necessary requirements for the level of preparation of primary school students according to the state educational standard and program for the formation of knowledge, skills and abilities in the process of training hard-of-hearing students to work, the technical stages of paper production for hard-of-hearing students, to have information about their creation processes, methods of working with paper, paper, types of paper and their characteristics, to acquire general concepts about professionals in the direction of paper production.